2011
DOI: 10.1111/j.1526-4637.2011.01200.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations in Tumor Necrosis Factor Alpha, Interleukin-10 Genes, and Migraine Susceptibility

Abstract: This study reflect that TNF-α-308G/A polymorphism may be one of the many genetic factors for migraine susceptibility in the Turkish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Migraine Type/Features Action in Relation to Migraine Dopamine type 2 (D2) receptor 23 Migraine with and without aura 23,91 • Vasoconstriction • Reduces trigeminal nerve activation • Inhibits release of vasoactive neuropeptide • Interrupts pain transmission centrally Glutathione S-transferase 92 Migraine without aura 92 • Increases susceptibility to environmental xenobioticinduced migraine attacks in GSTM1 genotype Dopamine type 4 (D4) receptor 93 Migraine without aura 93 • A potential genetic association exists between dopamine D4 receptor gene and migraine without aura Tumor necrosis factor-a 94 Migraine without aura 95 • Proinflammatory cytokine Methyltetrahydrofolate reductase (MTHFR) C677T allele 96 Migraine with aura 96 • MTHFR C677T polymorphism may increase homocysteine levels associated with migraine with aura Dopamine b-hydroxylase gene 97 Migraine with aura 97 • An intracellular enzyme catalyzing the conversion of dopamine to noradrenaline; imbalance may increase susceptibility to migraine Angiotensin-converting enzyme allele 98 Migraine with and without aura 90,99,100 • Involved in vasoconstriction and vascular remodeling…”
Section: Gene Productmentioning
confidence: 99%
“…Migraine Type/Features Action in Relation to Migraine Dopamine type 2 (D2) receptor 23 Migraine with and without aura 23,91 • Vasoconstriction • Reduces trigeminal nerve activation • Inhibits release of vasoactive neuropeptide • Interrupts pain transmission centrally Glutathione S-transferase 92 Migraine without aura 92 • Increases susceptibility to environmental xenobioticinduced migraine attacks in GSTM1 genotype Dopamine type 4 (D4) receptor 93 Migraine without aura 93 • A potential genetic association exists between dopamine D4 receptor gene and migraine without aura Tumor necrosis factor-a 94 Migraine without aura 95 • Proinflammatory cytokine Methyltetrahydrofolate reductase (MTHFR) C677T allele 96 Migraine with aura 96 • MTHFR C677T polymorphism may increase homocysteine levels associated with migraine with aura Dopamine b-hydroxylase gene 97 Migraine with aura 97 • An intracellular enzyme catalyzing the conversion of dopamine to noradrenaline; imbalance may increase susceptibility to migraine Angiotensin-converting enzyme allele 98 Migraine with and without aura 90,99,100 • Involved in vasoconstriction and vascular remodeling…”
Section: Gene Productmentioning
confidence: 99%
“…The genotype distribution of the included studies and the P-values for HWE testing are shown in Tables I and II. Main results, subgroup analyses. Six studies concerning the correlation between the TNF-α -308G/A polymorphism and migraine are shown in Table I (14) and Ghosh et al (15) revealed a significant association between the TNF-α -308G/A polymorphism and migraine risk. However, Hasan et al (16) revealed no significant association between the polymorphism and migraine and the results of Lee et al (17) were uncertain.…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%
“…In addition, among the included studies, one concerned only MO (12) and another only MA (13), three (15)(16)(17) clarified the clinical type of migraine and one (14) did not clarify the clinical type.…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study group consisted of 203 patients with migraine (25 male and 178 female; mean age: 36.49 ± 9.55 standard deviation [SD] years), and 202 (28 male and 174 female; mean age: 38.18 ± 8.42 SD years) healthy subjects who had taken part in our previous study [35]. All migraine patients were registered at the outpatient clinic of the Neurology Department at Gaziosmanpasa Medical Faculty, and they all fulfilled the International Headache Society criteria for classification [1].…”
Section: Subjectsmentioning
confidence: 99%